Effects of calcium supply on soybean plants - Fioreze, Samuel Luiz; Tochetto, Cláudia; Coelho, Antônio Eduardo; Melo, Heverton Fernando (Comunicata Scientiae, 2018)
This paper aims to evaluate the effects that calcium application on leaves and flowers of soybean plants exerts on yield and yield components. Two experiments were carried out in the 2013/2014 crop season under field conditions. In the first experiment, two soybean cultivars – one of determinate growth habit (BMX Ativa) and another of indeterminate growth habit (BMX Alvo) – were submitted to calcium spraying with four nozzles (twin flat, twin flat fan, cone and hollow cone). In the second experiment, soybean plants (BMX Ativa cultivar) were sprayed with calcium on the leaves and flowers at R1 or R3 growth stages. Subsequently, the plants were maintained or not under a 50-percent shade protection during flowering stage. Calcium spraying on soybean leaves or flowers during the flowering stage did not increase pod set, number of seeds, or grain yield. The calcium content in soybean flowers is not affected by foliar application thereof.